2017
DOI: 10.1377/hlthaff.2016.0966
|View full text |Cite
|
Sign up to set email alerts
|

Large Reductions In Amenable Mortality Associated With Brazil’s Primary Care Expansion And Strong Health Governance

Abstract: Strong health governance is key to universal health coverage. However, the relationship between governance and health system performance is underexplored. We investigated whether expansion of the Brazilian Estratégia de Saúde da Família (ESF; family health strategy), a community-based primary care program, reduced amenable mortality (mortality avoidable with timely and effective health care) and whether this association varied by municipal health governance. Fixed-effects longitudinal regression models were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 30 publications
7
75
0
9
Order By: Relevance
“…This precluded any potential analysis with SRRs for ACSC groups. Fifth, we used mortality from ACSCs as our outcome measure rather than the more broadly defined concept of healthcare-amenable mortality [30,46]). This was principally to focus on conditions that have been defined as amenable to PHC within the Brazilian context and to exclude those that may be strongly influenced by hospital-based care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This precluded any potential analysis with SRRs for ACSC groups. Fifth, we used mortality from ACSCs as our outcome measure rather than the more broadly defined concept of healthcare-amenable mortality [30,46]). This was principally to focus on conditions that have been defined as amenable to PHC within the Brazilian context and to exclude those that may be strongly influenced by hospital-based care.…”
Section: Discussionmentioning
confidence: 99%
“…Policy-makers should note that in Brazil, where sharp inequalities persist and an ambition to achieve UHC has been boldly pursued over the last 20 years, the equity-promoting associations of PHC are evident [30]. The strong positive relationship between PHC and reduced racial inequalities in mortality provides impetus for a renewed government commitment to the ESF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They will be our helping hands. The study led by researchers at Imperial College London, in collaboration with the data integration center at Fiocruz (CIDACS), found that a better level of governance and greater health coverage in primary care in Brazilian municipalities are associated with reduced mortality 19 . And the FHS may be the beginning of our long-awaited organized screening; • develop the feeling of nonconformity in mastologists who are in their "castle of knowledge" and to stop passively "accepting" the so common advanced stage lesions.…”
mentioning
confidence: 99%
“…Adherence to the programs is associated with public motivation and awareness. The low awareness rate in most developing countries is alarming and interventions to raise public awareness are needed 27 .…”
Section: Healthcare Usersmentioning
confidence: 99%